2014
DOI: 10.1370/afm.1677
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Implementation of Case Management for Patients With Dementia: A Systematic Mixed Studies Review

Abstract: PURPOSE Results of case management designed for patients with dementia and their caregivers in community-based primary health care (CBPHC) were inconsistent. Our objective was to identify the relationships between key outcomes of case management and barriers to implementation. METHODSWe conducted a systematic mixed studies review (including quantitative and qualitative studies). Literature search was performed in MEDLINE, PsycINFO, Embase, and Cochrane Library (1995 up to August 2012). Case management interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 88 publications
(143 reference statements)
4
61
0
2
Order By: Relevance
“…A number of systematic reviews have been reported of studies assessing the impact of case management on older people with dementia. [183][184][185][186][187][188][189] In general, studies have provided conflicting information about the potential benefits and duration of effect of case management for people with dementia. A recent Cochrane review of case management for PLWD found that the case management group was significantly less likely to be institutionalised at 6 and 12 months than those not receiving case management, although the longer-term effects were uncertain.…”
Section: Co-ordination and Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of systematic reviews have been reported of studies assessing the impact of case management on older people with dementia. [183][184][185][186][187][188][189] In general, studies have provided conflicting information about the potential benefits and duration of effect of case management for people with dementia. A recent Cochrane review of case management for PLWD found that the case management group was significantly less likely to be institutionalised at 6 and 12 months than those not receiving case management, although the longer-term effects were uncertain.…”
Section: Co-ordination and Navigationmentioning
confidence: 99%
“…These include strong provider and care networks, good personal connections with other HCPs, expert knowledge, embedding in the multidisciplinary team, the involvement of GPs, intensive and proactive approaches and clearly defined skills and responsibilities. 184,188,[192][193][194] An example in which care for people with dementia is reported to have been successfully co-ordinated in the UK is the Oxleas Advanced Dementia Service, which provides care co-ordination, palliative care and support to people with advanced dementia living at home. 195 The authors of this report provide key lessons that they have learned: the need to provide care and advice to family carers; strong links between physical and mental health services; acceptance of referrals from a wide range of HCPs; a single comprehensive assessment of the patient and carer that addresses physical, mental health and social care needs; for a personalised care plan; and dedicated care co-ordination by a specialist nurse with suitable case management skills.…”
Section: Co-ordination and Navigationmentioning
confidence: 99%
“…[14][15][16][17][18][20][21][22] Our previous studies demonstrated that the effectiveness of CM depends on a small caseload, regular and proactive follow-up, and transparent communication among health care professionals. 110,111 Limitations As in any systematic review, we may have missed studies that we should have included. It is unlikely, however, that we missed large studies, as the literature search was comprehensive and included publications in 3 languages (English, French, and Russian).…”
Section: Discussionmentioning
confidence: 99%
“…Desde el primer momento, es importante también involucrar al cuidador del paciente y tener la información médica necesaria que indique el nivel de deterioro de las capacidades cognitivas del paciente (12,23,32,33).…”
Section: B Sintomatologíaunclassified
“…Por ejemplo, para el cumplimiento a la cita: darla por escrito, utilizar mensajes de texto, además de la llamada de rutina utilizada para confirmar la cita y poner letreros de recordación en las zonas donde realizan la higiene, pueden ser de ayuda (4,6,28,32,34).…”
Section: Salud Oral En La Etapa Inicial De La Demencia Y Su Manejounclassified